2009
DOI: 10.1002/cctc.200900209
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Alumina‐Supported Silver Cluster for N‐Benzylation of Anilines with Alcohols

Abstract: An alumina‐supported silver cluster with a Lewis acidic cocatalyst (polyvalent metal salts, such as FeCl3⋅6 H2O) acts as a heterogeneous and recyclable catalyst for the direct N‐alkylation of anilines with benzyl alcohols, which is driven by the borrowing hydrogen mechanism. Systematic studies on the effects of metal (Pt, Pd, Au, and Ag), silver particle size, support oxides (CeO2, ZrO2, Al2O3, SiO2), and Lewis acidic additives show four important factors required to achieve selective N‐alkylation of anilines:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(69 citation statements)
references
References 73 publications
1
68
0
Order By: Relevance
“…However, recently developed heterogeneous systems based on Raney-Ni 120) suffer from high catalyst loading (370-440 mol% with respect to nitro benzene), a limited scope, and harsh reaction conditions (1-3 MPa H2). Based on our findings that Ag/ Al2O3 heterogeneously catalyze alcohol dehydrogenation 45) , hydrogenation of nitro groups by H2 50) , one-pot reactions driven by the borrowing-hydrogen mechanism 48), 49) , we showed the first example of the heterogeneous catalysis of the direct synthesis of N-substituted amines from nitrobenzenes and alcohols under 0.2 MPa H2 driven by the borrowing-hydrogen mechanism (Fig. 10).…”
Section: Selective Hydrogenation Of Nitroaromaticsmentioning
confidence: 85%
See 1 more Smart Citation
“…However, recently developed heterogeneous systems based on Raney-Ni 120) suffer from high catalyst loading (370-440 mol% with respect to nitro benzene), a limited scope, and harsh reaction conditions (1-3 MPa H2). Based on our findings that Ag/ Al2O3 heterogeneously catalyze alcohol dehydrogenation 45) , hydrogenation of nitro groups by H2 50) , one-pot reactions driven by the borrowing-hydrogen mechanism 48), 49) , we showed the first example of the heterogeneous catalysis of the direct synthesis of N-substituted amines from nitrobenzenes and alcohols under 0.2 MPa H2 driven by the borrowing-hydrogen mechanism (Fig. 10).…”
Section: Selective Hydrogenation Of Nitroaromaticsmentioning
confidence: 85%
“…Studies on structureactivity relationship suggested that the reaction proceeds by a cooperation of coordinatively unsaturated Ag site and acid-base sites of Al2O3 support. 49) It is well known that hydrogen interacts only very weakly with extended Ag surfaces (single crystals, polycrystalline surfaces), and dissociative chemisorption of H2 do not occur at low temperature 100) . This is attributed to the completely filled d-band of Ag as well as the position of the d-band center relative to the Fermi level 7) .…”
Section: )mentioning
confidence: 99%
“…The first dehydrogenation step was presumed to be irreversible [14,23], while for the second and third steps the reverse reactions were also taken into account.…”
Section: Kinetic Modelingmentioning
confidence: 99%
“…The one-pot alcohol amination has been studied actively in the presence of homogeneous catalysts [10][11][12] as well as different heterogeneous metal catalysts [13][14][15][16][17]. However, the process kinetics has been described only to a limited extent.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Following this pioneering work, a number of transition metals such as Mo, [3] Fe, [4] Pd, [5] Pt, [6] Au [7] and Ag [8] have been demonstrated to efficiently catalyze this type of reaction. Very recently, a first enantioselective direct amination of an allylic alcohol has been realized in an intramolecular fashion via the action of an HgA C H T U N G T R E N N U N G (OTf) 2 catalyst.…”
Section: Introductionmentioning
confidence: 99%